Bluestar’s acquisition of Adisseo (c) - Li, Donghong; Yang, Zhuge; Li, Xiaohui, active 2024 (London : Tsinghua University School of Economics and Management, 2024)
In cross-border mergers and acquisitions (M&A), post-merger integration is a challenge. The main questions posed are how should the expected operating and financial targets and a smooth transition be achieved and synergies be generated. These factors directly affect the ultimate realization of the value of overseas M&A transactions. This case, as the third one in the series of cases on BlueStar’s acquisition of Adisseo, highlights new strategic initiatives adopted by the Bluestar Group in recent years to boost Adisseo’s growth. Furthermore, this case focuses on the promotion of further integration between the Bluestar Group and Adisseo at various levels since the completion of the acquisition of and integration with Adisseo in 2012. The case focuses on the following questions: How did China National Chemical Corporation Ltd. (ChemChina) and the Bluestar Group promote the successful listing of Adisseo, the acquired company in China’s A-share market? How did the A-share listing transform Adisseo’s corporate governance? Backed by the Bluestar Group and ChemChina, which initiatives did Adisseo take in terms of related diversification, capacity expansion, and global layout? How did ChemChina and the Bluestar Group further promote the merger and integration, as well as the sustainable development of Adisseo? Which innovative practices were adopted by the parties and how did they benefit? These explorations and practices provide useful experience for Chinese companies’ M&A of overseas companies and integration after.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations -- Case studies